Revolusi Pendidikan dengan Artificial Intelligence: Peluang dan Tantangan - Erna Widyasari; Budi Murtiyasa; Eko Supriyanto (Jurnal Ilmiah Edukatif, 2024)
The use of Artificial Intelligence (AI) in education offers tremendous opportunities to improve personalization of learning, administrative efficiency, and accessibility of education at scale. AI can quickly analyze student data, provide real-time learning recommendations, and ease the administrative burden on teachers, freeing them up to focus on teaching. However, the application of AI in education also presents significant challenges, such as inequitable access to technology and potential bias in algorithms that could exacerbate existing inequities. To address these challenges and maximize the benefits of AI, collaboration between governments, educational institutions, and technology providers is needed to ensure that AI integration is done in an inclusive, equitable, and ethical manner.